The Glory on the Mountain: The Episode of the Transfiguration of Jesus - Puig i Tàrrech, Armand (New Testament studies, 2012)
The starting point of the transfiguration of Jesus is the choice of Jesus himself. He had announced a destiny of suffering and death and, then, was faced with rejection of his words by his disciples, especially Peter. Now, they must know by themselves what ‘God's views’ are. The fundamental issue is whether Jesus' announcement really corresponds to the divine will. The answer will come from heaven: the disciples will be the privileged witnesses of the transfiguration granted to Jesus. He will appear as a heavenly figure, flanked by Moses and Elijah and thus preceding them. Peter would like to honour the three figures and prolong the wonderful vision making three dwelling-places, which recall the heavenly dwellings. But he does not realize that Jesus had announced a tragic destiny that falls within God's design. So, God has to speak. After the cloud will cover the three heavenly figures, the divine voice will address the disciples making it clear to them who Jesus is (God's Son) and what they must do (listen to Jesus, namely, accept his announcement of suffering and death).